2015
DOI: 10.1002/tox.22125
|View full text |Cite
|
Sign up to set email alerts
|

Fipronil induced oxidative stress involves alterations in SOD1 and catalase gene expression in male mice liver: Protection by vitamins E and C

Abstract: In the present investigation, hepatic oxidative stress induced by fipronil was evaluated in male mice. We also investigated whether pretreatment with antioxidant vitamins E and C could protect mice against these effects. Several studies conducted in cell lines have shown fipronil as a potent oxidant; however, no information is available regarding its oxidative stress inducing potential in an animal model. Out of 8 mice groups, fipronil was administered to three groups at low, medium, and high dose based on its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
21
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 32 publications
10
21
2
1
Order By: Relevance
“…We evaluated the expression of SOD-1, with catalytic activity in the cytosol and requiring copper and zinc as a cofactor for its enzymatic activity. Although some authors have found that oxidative stress induces the expression of SOD in other tissues [29, 30], we have not found significant differences in the expression of this enzyme, possibly because catalyzing reaction is not favored in the presence of high levels of hydrogen peroxide.…”
Section: Discussioncontrasting
confidence: 92%
“…We evaluated the expression of SOD-1, with catalytic activity in the cytosol and requiring copper and zinc as a cofactor for its enzymatic activity. Although some authors have found that oxidative stress induces the expression of SOD in other tissues [29, 30], we have not found significant differences in the expression of this enzyme, possibly because catalyzing reaction is not favored in the presence of high levels of hydrogen peroxide.…”
Section: Discussioncontrasting
confidence: 92%
“…As the human lifespan increases, research will be focused on issues facing the elderly, such as oxidative stress, which contributes to tumors, Alzheimer's disease, type 2 diabetes, obesity, cardiovascular disease, and age-related macular degeneration (Bakala et al, 2012;Badgujar et al, 2016). Under normal physiological condition, free radicals and reactive oxygen species (ROS), including superoxide anions (O 2 − ), hydrogen peroxide (H 2 O 2 ), hydroxyl radicals ( • OH), and peroxynitrite (ONOO − ) are generated from aerobic metabolism (Bonomini et al, 2015); however, an imbalance between endogenous antioxidants and accumulation of ROS causes oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…The DNT status of fipronil is not yet finally agreed on. Several in vivo studies describe neurotoxic effects of fipronil in zebrafish development (Stehr et al 2006;Park et al 2020), rats (Cravedi et al 2013;Abdel-Daim et al 2019) and mice (Badgujar et al 2016). In vivo testing of chemicals in vertebrates is cost-intensive and raises severe ethical concerns (Russell and Burch, 1959).…”
Section: Introductionmentioning
confidence: 99%